2017
DOI: 10.1007/s00453-017-0354-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Static and Self-Adjusting Parameter Choices for the $$(1+(\lambda ,\lambda ))$$ ( 1 + ( λ , λ ) ) Genetic Algorithm

Abstract: The (1 + (λ, λ)) genetic algorithm (GA) proposed in [Doerr, Doerr, and Ebel. From black-box complexity to designing new genetic algorithms. Theoretical Computer Science (2015)] is one of the few examples for which a super-constant speed-up of the expected optimization time through the use of crossover could be rigorously demonstrated. It was proven that the expected optimization time of this algorithm on OneMax is O(max{n log(n)/λ, λn}) for any offspring population size λ ∈ {1, . . . , n} (and the other param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 117 publications
(105 citation statements)
references
References 61 publications
1
101
0
3
Order By: Relevance
“…Proof (of Theorem 2). We partition the search space Y into the sets A (j, ) from Definition 4, where j ∈ [0..k − 1] and ∈ [d j ], along with A (k,1) , and define A ≥(j, ) as in (12).…”
Section: Applying the Level-based Theoremmentioning
confidence: 99%
“…Proof (of Theorem 2). We partition the search space Y into the sets A (j, ) from Definition 4, where j ∈ [0..k − 1] and ∈ [d j ], along with A (k,1) , and define A ≥(j, ) as in (12).…”
Section: Applying the Level-based Theoremmentioning
confidence: 99%
“…The performance curves for success rates ≥ 4 seem to be roughly U-shaped with different values of A in which the minimum is obtained. It could be worthwhile to extend the mathematical analysis of the dyn (1, 1, 1, A, b) presented in [DD18a] in order to identify the precise relationship.…”
Section: Influence Of the Update Strengthsmentioning
confidence: 99%
“…Next we turn our attention to the five-dimensional (1 + (λ, λ)) GA variant dyn(α, β, γ, A, b), in which not only the update strengths A and b are configurable, but also the dependence of p = αλ/n, λ 2 = nint(βλ), c = γ/λ. The dependencies of the parameters on λ are based on a theoretical result proven in [DD18a], where it is shown that any static configuration with λ 2 = λ 1 (i.e., A = b = β = 1) that achieves optimal asymptotic expected performance must necessarily satisfy p = Θ(λ/n) and γ = Θ(1/λ).…”
Section: -Dimensional Parameter Tuningmentioning
confidence: 99%
See 2 more Smart Citations